Integrating Ambient Assisted Living into Nursing Education: Are We Ready for the Future of Gerontechnology? - Songwathana, Praneed; Muanjan, Montira (Pacific Rim International Journal of Nursing Research)
The accelerating global shift toward ageing populations has become one of the most urgent challenges for 21st-century health systems and nursing education. As nations strive to prepare digitally competent health workforces, technologies such as simulation-based learning, virtual reality, artificial intelligence, and ambient assisted living (AAL) are redefining what it means to care for older adults with independence, dignity, and safety. AAL refers to intelligent environments and systems designed to support disability-free and independent living while enhancing the well-being of older users. Yet, the promise of AAL remains unevenly realized. While high-income countries have incorporated gerontechnology into curricula and practice, many middle-income nations, including Thailand, still rely on traditional pedagogy, leaving graduates underprepared for the realities of digital health. This editorial argues that integrating AAL into nursing education is no longer optional but essential. It calls for a paradigm shift that positions AAL as a global core competency aligned with the United Nations Sustainable Development Goals Goal 3 (Good Health and Well-being) and Goal 4 (Quality Education) and the Universal Health Coverage (UHC) principles of efficiency, equity, and effectiveness. The readiness of today's nursing education to embrace AAL in curricula, teaching-learning, and digital infrastructure will determine not only how well future nurses are prepared for geriatric care but also how effectively health systems keep pace with the global, gerontechnology-driven transformation.